Current Status of Companion and Complementary Diagnostics: Strategic Considerations for Development and Launch. Issue 2 (27th February 2017) - Scheerens, H; Malong, A; Bassett, K; Boyd, Z; Gupta, V; Harris, J; Mesick, C; Simnett, S; Stevens, H; Gilbert, H; Risser, P; Kalamegham, R; et al.
Abstract : US Food and Drug Administration (FDA)‐approved diagnostic assays play an increasingly common role in managing patients to prolong lifespan while also enhancing quality of life. Diagnostic assays can be essential for the safe and effective use of therapeutics ( companion diagnostic ), or may inform on improving the benefit/risk ratio without restricting drug access ( complementary diagnostic ). This tutorial reviews strategic considerations for drug and assay development resulting in FDA‐approved companion or complementary diagnostic status.